PENGARUH PROFITABILITAS, LEVERAGE, DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR ENERGI - Muliawan, Leandro Keefe Arie; Susanto, Liana (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This research is aiming to obtain empirical evidences about the impact of profitability, leverage, and liquidity on firm value in energy sector companies that are listed on the Indonesia Stock Exchange on 2019-2021. There are 41 companies selected as sample through purposive sampling method. Data processing techniques use multiple regression analysis that are helped by SPSS program (Statistical Product and Service Solution) for Windows 25 and Ms. Excel 2013. The results shows on this study indicate that profitability and leverage have significant positive effect for firm value, then liquidity does not have a significant effect on firm value. The implication of this study is the importance of observing the profitability and leverage ratio that will increase the firm value which will bring a good satisfactory for the investors.